PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP RETURN SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Ananta, Putri; Triani, Neks; Kumalasari, Fitri (Jurnal Akuntansi Kompetif, 2025)
This research investigates the influence of profitability and solvency in stock returns in banking institututions listed on the Indonesia stock exchange (IDX) between 2019 and 2023. Employing a quantitative approach, the study uses secondary data sourced from the financial statements of listed banks over that period. Data analysis was conducted using multiple linear regression with the assistance of Spss version 29. The findings reveal that return on asset (ROA) and return on equity (ROE) each have a statistically significant effect on stock returns, with p-values of 0.014 and 0.001, respectively both well below the 0.05 threshold. Additionally, earnings per share (EPS) emerged as a strong contributing factor, showing a p-value of 0.010. in the context of solvency, the debt t equity ratio (DER) also demonstrated a meaningful impact on stock returns, with a confidence level of 95%. The robustness of the model is further supported by the overasll low p-value, affirming the relevance of the these financial indicators in predicting stock return behavior. Keywords: Profitability, Solvency, stock Return, Banking sector, Indonesia Stock Exchanges